Electronically-Controlled Active-C Filters and Equalizers with Operational Transconductance Amplifiers - Malvar, Henrique S.; Malvar, Henrique S. (IEEE Transactions on Circuits and Systems, 1984)
Current-controlled filters and euqalizers that employ operational transconductance amplifiers (OTAs) and capacitors are presented. Those circuits can be integrated in bipolar technology and are characterized by good linearity between controlled parameteres and their respective control currents.